Educational and rehabilitation service utilization in adolescents born preterm or with a congenital heart defect and at high risk for disability. (17th August 2017) - Majnemer, Annette; Dahan‐Oliel, Noemi; Rohlicek, Charles; Hatzigeorgiou, Sean; Mazer, Barbara; Maltais, Desiree B; Schmitz, Norbert
Abstract : Aim: This historical cohort study describes the use of educational and rehabilitation services in adolescents born preterm or with a congenital heart defect (CHD). Method: Parents of 76 young people (mean age 15y 8mo [SD 1y 8mo]) with CHD and 125 born ≤29 weeks gestational age (mean age 16y [SD 2y 5mo]) completed a demographics questionnaire including educational and rehabilitation resource utilization within the previous 6 months. Rehabilitation services included occupational therapy, physical therapy, speech language pathology, psychology. Developmental (Leiter Brief IQ, Movement‐ABC, Strengths and Difficulties Questionnaire) and functional (Vineland) status of the young people was assessed. Pearson χ 2 tests were used to perform simple pairwise comparisons of categorical outcomes across the two groups (CHD, preterm). Univariate logistic regression was used to examine predictors of service utilization. Results: Developmental profiles of the two groups (CHD/preterm) were similar (29.9%/30% IQ<80; 43.5%/50.0% motor difficulties; 23.7%/22.9% behavior problems). One‐third received educational supports or attended segregated schools. Only 16% (preterm) and 26.7% (CHD) were receiving rehabilitation services. Services were provided predominantly in the school setting, typically weekly. Few received occupational therapy or physical therapy (1.3–7.6%) despite functional limitations. Leiter Brief IQ<70 was associated with receiving educational supports (CHD: OR 5.53, 95% CI 1.29–23.68; preterm: OR 14.63, 3.10–69.08) and rehabilitation services (CHD: OR 4.46, 1.06–18.88; preterm: OR 5.11, 1.41–18.49). Young people with motor deficits were more likely to require educational (CHD: OR 5.72, 1.99–16.42; preterm: OR 3.11, 1.43–6.77) and rehabilitation services (preterm: OR 3.97, 1.21–13.03). Interpretation: Although young people with impairments were more likely to receive educational and rehabilitation services, many may not be adequately supported, particularly by rehabilitation specialists. Rehabilitation services at this important transition phase could be beneficial in optimizing adaptive functioning in the home, school, and community. What this paper adds: Young people with congenital heart defect have a similar developmental profile to those born preterm. Supports provided to neonatal intensive care unit survivors in adolescence seem focused on educational services. Rehabilitation services are not received despite functional limitations. This article's abstract has been translated into Spanish and Portuguese. Follow the links from theabstract to view the translations.